Strengthening Student Engagement in Learning Through Use of Digital Tools - Girdzijauskienė, Rūta; Norvilienė, Aida; Šmitienė, Gražina; Rupšienė, Liudmila (Acta Paedagogica Vilnensia, 2022)
This paper analyzes teaching and learning in the context of the implementation of digital technology in educational practices. On the basis of the data obtained from focus group discussions and creative workshops with primary school teachers, ways are identified to recognize and strengthen student engagement in learning through the use of digital tools, based on artificial intelligence and integrating learning analytics. As evidenced by the analysis of the research data, students’ cognitive, emotional, and behavioral engagement in learning increases due to the use of digital learning tools. To support and strengthen student engagement, teachers need to rethink their habitual educational practices, anticipate the barriers to engagement caused by digital technologies and the ways of coping with them, make use of digital tools for personalized and in-depth learning, and apply effective means to manage classrooms and interactions between students.